Bonding Efficacy of New Self-etching, Self-adhesive Dual-curing Resin Cements to Dental Enamel - Benetti, Paula [UNESP]; Boas Fernandes Junior, Virgilio Vilas [UNESP]; Gomes Torres, Carlos Rocha [UNESP]; Pagani, Clovis [UNESP] (Quintessence Publishing Co Inc, 2011)
Purpose: This study evaluated the efficacy of the union between two new self-etching self-adhesive resin cements and enamel using the microtensile bond strength test.Materials and Methods: Buccal enamel of 80 bovine teeth was submitted to finishing and polishing with metallographic paper to a refinement of #600, in order to obtain a 5-mm(2) flat area. Blocks (2 x 4 x 4 mm) of laboratory composite resin were cemented to enamel according to different protocols: (1) untreated enamel + RelyX Unicem cement (RX group); (2) untreated enamel + Bifix SE cement (BF group); (3) enamel acid etching and application of resin adhesive Single Bond + RelyX Unicem (RXA group); (4) enamel acid etching and application of resin adhesive Solobond M + Bifix SE (BFA group). After 7 days of storage in distillated water at 37 degrees C, the blocks were sectioned for obtaining microbar specimens with an adhesive area of 1 mm(2) (n = 120). Specimens were submitted to the microtensile bond strength test at a crosshead speed of 0.5 mm/min. The results (in MPa) were analyzed statistically by ANOVA and Tu key's test.Results: Enamel pre-treatment with phosphoric acid and resin adhesive (27.9 and 30.3 for RXA and BFA groups) significantly improved (p <= 0.05) the adhesion of both cements to enamel compared to the union achieved with as-polished enamel (9.9 and 6.0 for RX and BF).Conclusion: Enamel pre-treatment with acid etching and the application of resin adhesive significantly improved the bond efficacy of both luting agents compared to the union achieved with as-polished enamel.
Keywords: enamel; acid etching; adhesives; luting agents; tensile bond strength